Why urban Indians are interested in an internet based self-care app for depression? a brief pilot survey - Mehrotra, Seema; C. R., Satish Kumar; Gandotra, Aditi; Sudhir, Paulomi M.; Thirthalli, Jagadisha; Rao, Girish N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Digital technology has emerged as a powerful approach to bridge treatment gap in the field of mental health. However, public health impact of e-interventions is unlikely without large scale uptake of such services. Hence it becomes important to understand motives of potential users in order to design programs that address such needs as well as disseminate information about the same in ways that appeal to the users. Methods: Reasons underlying interest in an internet based self-care program for depression were explored through a brief survey of potential users who had explicitly shown interest in such a program. Responses to an online survey were received from 120 respondents out of which about 69% were in 18-35 years of age-range and 12% were above 50 years of age. Results: Preference for flexibility in terms of ‘when I do things to help myself’, ‘not having time to go for face to face counselling/therapy’ and ‘wanting to learn and do something to prevent problems in future even though I am currently on treatment’ emerged as the top 3 reasons underlying interest in internet based self-help programs for depression. Not having the finances to seek face to face mental health consultation emerged as one of the top 3 reasons in the older group. Conclusions: Incorporating maximal flexibility, providing pointers to the most relevant components thereby minimizing time required, and focusing on preventive strategies (even for those who are currently seeking treatment) are aspects that need to be considered in development and dissemination of internet based self-help programs for depression in urban India.